Analysis of accuracy of statistical forecasting of the atmospheric temperature - V. S. Mukha (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Empirical data about precision of linear statistical forecast of the atmospheric temperature in comparison with precision of the climatological and numerical forecasts is given and analyzed.